Amorphous iron phosphate and preparation method thereof, and anhydrous iron phosphate and preparation method thereof

By adjusting the pH value and temperature of the ferrous phosphate slurry, amorphous iron phosphate with low iron hydroxide content is generated, and anhydrous iron phosphate is synthesized through crystallization and decrystallization hydration, the problem of improving the performance of lithium iron phosphate positive electrode material is solved, and anhydrous iron phosphate with high specific surface area and low agglomeration is achieved.

CN119706765AActive Publication Date: 2025-03-28JIUJIANG TINCI ADVANCED MATERIALS CO LTD +1

Patent Information

Application Number
CN202411741822.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-28
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

There is still room for improvement in the compaction density and electrochemical performance of existing lithium iron phosphate cathode materials, and their morphology and structure have a decisive impact on performance.

Method used

By preparing solution A with a phosphorus source and ferrous ferrous source, adjusting the pH value and temperature, the reaction is to form a ferrous phosphate slurry, and amorphous iron phosphate with low iron hydroxide content is obtained through oxidation. The amorphous iron phosphate subsequently conventional crystallization and decrystallization hydration synthesize anhydrous iron phosphate.

Benefits of technology

The uniform particle size distribution of amorphous iron phosphate is achieved, the degree of agglomeration is low and the particle size is small, thereby improving the specific surface area and electrochemical properties of anhydrous iron phosphate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706765A_ABST
    Figure CN119706765A_ABST
Patent Text Reader

Abstract

The invention provides amorphous iron phosphate, the X-ray diffraction pattern of the amorphous iron phosphate has a first diffraction peak theta 1 and a second diffraction peak theta 2 at 19-21 degrees and 28-30 degrees respectively, and the ratio of the peak intensity I1 of the first diffraction peak to the peak intensity I2 of the second diffraction peak is 0.8-0.91; the amorphous iron phosphate is spherical or sphere-like particles. The amorphous iron phosphate has the advantages of low ferric hydroxide content, uniform particle size distribution, small primary particle size and low agglomeration degree, and is beneficial to subsequent preparation of iron phosphate with high specific surface area, small primary particle size and low agglomeration. The invention also provides a preparation method of the amorphous iron phosphate and anhydrous iron phosphate prepared based on the amorphous iron phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery materials, and in particular relates to the modification of anhydrous iron phosphate intermediates and anhydrous iron phosphate. Background Art

[0002] Among the positive electrode materials of lithium-ion batteries, lithium iron phosphate has become a hot research topic for positive electrodes of lithium-ion batteries due to its advantages of being non-toxic, cheap, and safe. With the development of new energy power generation and energy storage, household energy storage and other usage scenarios, the cost and long cycle performance advantages of lithium iron phosphate have become more prominent, and it has been widely used in automobiles and large-scale energy storage applications. However, the compaction density and electrochemical properties of lithium iron phosphate still need to be improved. As the skeleton of lithium iron, the morphology and structure of iron phosphate play a decisive role in the compaction density and electrochemical properties of lithium iron phosphate. Therefore, studying the preparation process of iron phosphate with controllable particle distribution has high application value and research significance. Summary of the invention

[0003] In response to the above technical problems, the present application provides amorphous ferric phosphate and a preparation method thereof, anhydrous ferric phosphate and a preparation method thereof.

[0004] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, an amorphous iron phosphate is provided, wherein an X-ray diffraction spectrum of the amorphous iron phosphate has a first diffraction peak θ1 and a second diffraction peak θ2 at 19-21° and 28-30°, respectively, and a ratio of a peak intensity I1 of the first diffraction peak to a peak intensity I2 of the second diffraction peak is 0.8-0.91, and the amorphous iron phosphate is a spherical or quasi-spherical particle.

[0005] Furthermore, 95% of the primary particles of the amorphous iron phosphate have a particle size of less than 80 nm.

[0006] In a second aspect, a method for preparing amorphous ferric phosphate is provided, comprising: A solution A is prepared by using a phosphorus source and a ferrous source, and the pH value and temperature of the solution A are adjusted to react to obtain an off-white ferrous hydrogen phosphate slurry; The off-white ferrous hydrogen phosphate slurry is oxidized to obtain yellow amorphous ferric phosphate slurry, and the amorphous ferric phosphate is obtained by solid-liquid separation and washing.

[0007] Further, the pH value of solution A is adjusted to 1.5-3.5.

[0008] Furthermore, the reagent for adjusting the pH of solution A is one or more of ammonia water, urea, and sodium hydroxide.

[0009] Further, the temperature of solution A is adjusted to 40-60 o C.

[0010] Furthermore, the phosphorus source is one or two of diammonium phosphate, phosphoric acid, diammonium hydrogen phosphate, and ammonium phosphate.

[0011] Furthermore, the ferrous source is one or more of ferrous sulfate, ferrous chloride, ferrous nitrate, iron powder, ferrous oxide, and ferrous oxalate.

[0012] Furthermore, the molar ratio of the phosphorus source calculated as phosphate to the ferrous source calculated as iron element is 0.95-1.2:1.

[0013] Furthermore, the oxidant used in the oxidation is one or more of hydrogen peroxide, air, oxygen, and ozone.

[0014] Furthermore, the amount of the oxidant used is 1.2 to 1.4 times the theoretically required amount.

[0015] Furthermore, in the solution A, the mass percentage concentration of phosphorus element is 2-5%.

[0016] Furthermore, in the solution A, the mass percentage concentration of the iron element is 3-7%.

[0017] Furthermore, the pH value of the solution A is 0.5<pH<1.2.

[0018] Furthermore, the raw materials for preparing the solution A also include an acidic solution or an alkaline solution; the acidic solution is one or more of sulfuric acid and hydrochloric acid, and the alkaline solution is one or more of ammonia water, urea solution, and sodium hydroxide solution.

[0019] Furthermore, the washing is performed with pure water; preferably, the conductivity of the washing water at the end point of the washing is not greater than 20000 μS / cm.

[0020] In a third aspect, anhydrous ferric phosphate is provided, wherein the synthetic raw material is the aforementioned amorphous ferric phosphate or the amorphous ferric phosphate prepared by the aforementioned preparation method; 95% of the primary particles of the anhydrous ferric phosphate have a particle size of less than 90 nm, a specific surface area of ​​9-14 m² / g, and a tap density of 0.7-1.0 g / cm³.

[0021] In a fourth aspect, a method for preparing anhydrous ferric phosphate is provided, comprising: The aforementioned amorphous ferric phosphate or the amorphous ferric phosphate prepared by the aforementioned preparation method is mixed with a phosphoric acid solution, heated for crystallization, filtered, washed with water, and calcined to obtain anhydrous ferric phosphate.

[0022] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The present application provides amorphous iron phosphate, wherein the peak intensity ratio of the first diffraction peak to the second diffraction peak corresponding to 19-21° and 28-30°, respectively, of the amorphous iron phosphate is 0.8-0.91, the amorphous iron phosphate has a low amount of iron hydroxide, a uniform primary particle size distribution, a small primary particle size, and a low degree of agglomeration, which is conducive to the subsequent preparation of iron phosphate with a high specific surface area, a small primary particle size, and low agglomeration.

[0023] The preparation method of amorphous ferric phosphate provided in the present application uses a divalent iron source and a phosphorus source as raw materials, first reacts to generate ferrous hydrogen phosphate slurry, and then obtains an amorphous ferric phosphate material with a low iron hydroxide content by oxidation. The amorphous ferric phosphate material has a low iron hydroxide content, a uniform particle size distribution, a small primary particle size, and a low degree of agglomeration, which is conducive to the subsequent preparation of iron phosphate with a high specific surface area, a small primary particle size, and low agglomeration. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 The XRD diagrams of amorphous iron phosphate prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown.

[0026] Figure 2 The SEM image and particle distribution diagram of the amorphous iron phosphate prepared in Example 1.

[0027] Figure 3 The SEM image and particle distribution diagram of the anhydrous ferric phosphate prepared in Example 1.

[0028] Figure 4 This is the XRD pattern of the anhydrous iron phosphate prepared in Example 1.

[0029] Figure 5 The SEM image and particle distribution diagram of the amorphous iron phosphate prepared in Comparative Example 1.

[0030] Figure 6 The SEM image and particle distribution diagram of the anhydrous ferric phosphate prepared in Comparative Example 1.

[0031] Figure 7 This is the XRD pattern of anhydrous iron phosphate prepared in Comparative Example 1.

[0032] Figure 8 The SEM image and particle distribution diagram of the amorphous iron phosphate prepared in Comparative Example 2.

[0033] Fig. 9 The SEM image and particle distribution diagram of the anhydrous ferric phosphate prepared in Comparative Example 2.

[0034] Fig.10 This is the XRD pattern of anhydrous iron phosphate prepared in Comparative Example 2.

[0035] in, Figure 2 , 3 The particle distribution diagrams in , 5, 6, 8, and 9 were obtained by statistically processing the SEM images using Image J software. DETAILED DESCRIPTION

[0036] At present, the production process of iron phosphate on the market is mainly based on a two-step method. First, the phosphorus source and the trivalent iron source are neutralized to form amorphous iron phosphate. The amorphous iron phosphate has low crystallinity and spherical particles. It contains metal ions such as sulfate, ammonium, and manganese. Then, the amorphous iron phosphate is transformed into a crystal form and excess impurities are removed to form dihydrate iron phosphate. The specific surface area of ​​dihydrate iron phosphate is relatively high, usually around 50m 2 / g, and finally dehydrated to form anhydrous iron phosphate, the particles are spherical, and the secondary particles form porous agglomerates without specific morphology. This process usually results in serious agglomeration of materials, large particles, low specific surface area, and difficulty in subsequent crushing. At the same time, a large number of pores between particles are not filled with particles, which reduces the compaction density. During the charge and discharge process, some particles are overcharged and over-discharged, affecting the electrochemical performance. At the same time, there are many factors affecting the synthesis process of iron phosphate, and there is currently little research on the products of the amorphous iron phosphate process.

[0037] The applicant discovered during the process of synthesizing anhydrous ferric phosphate that synthesizing amorphous ferric phosphate with a low iron hydroxide content is beneficial to improving the particle size distribution of amorphous ferric phosphate and reducing agglomeration and primary particle size; further, the intermediate amorphous ferric phosphate is subsequently subjected to conventional crystallization and dehydration to synthesize anhydrous ferric phosphate, and during the crystallization process, the inorganic acid diffuses into the interior of the intermediate amorphous ferric phosphate to react, remove the iron hydroxide and achieve crystallization. Since the intermediate amorphous ferric phosphate is an amorphous ferric phosphate with low agglomeration and good dispersibility, the ferric phosphate obtained after crystallization and dehydration can continue the morphological characteristics of the amorphous ferric phosphate, and can synthesize anhydrous ferric phosphate with a small primary particle size, low agglomeration and high specific surface area. Based on this, the present invention is completed.

[0038] The present invention provides an amorphous iron phosphate, wherein an X-ray diffraction spectrum of the amorphous iron phosphate has a first diffraction peak θ1 and a second diffraction peak θ2 at 19-21° and 28-30°, respectively, and a ratio of a peak intensity I1 of the first diffraction peak to a peak intensity I2 of the second diffraction peak is 0.8-0.91, and the amorphous iron phosphate is a spherical or quasi-spherical particle.

[0039] In the above technical solution, the characteristic peaks at 19-21° belong to iron hydroxide and iron phosphate, and the characteristic peaks at 28-30° belong to iron phosphate. Therefore, the ratio of peak intensity I1 / I2 can reflect the content of iron hydroxide in amorphous iron phosphate.

[0040] In some preferred embodiments, the ratio of the peak intensity I1 of the first diffraction peak to the peak intensity I2 of the second diffraction peak is 0.82~0.905, for example, 0.82, 0.825, 0.83, 0.835, 0.84, 0.845, 0.85, 0.855, 0.86, 0.865, 0.87, 0.875, 0.88, 0.885, 0.89, 0.895, 0.90, 0.905, etc.

[0041] In some preferred embodiments, 95% of the primary particles of the amorphous iron phosphate have a particle size of less than 80 nm, more preferably between 20 and 80 nm, and more preferably between 20 and 70 nm, such as 20 to 70 nm, 20 to 60 nm, etc. The primary particles of the amorphous iron phosphate have a small particle size and a uniform particle size distribution.

[0042] The present invention provides a method for preparing amorphous ferric phosphate, comprising: A solution A is prepared by using a phosphorus source and a ferrous source, and the pH value and temperature of the solution A are adjusted to react to obtain an off-white ferrous hydrogen phosphate slurry; The off-white ferrous hydrogen phosphate slurry is oxidized to obtain yellow amorphous ferric phosphate slurry, and the amorphous ferric phosphate is obtained by solid-liquid separation and washing.

[0043] The applicant has found through research that by using a divalent iron source and a phosphorus source to first carry out a neutralization reaction (by adjusting the pH), forming a ferrous hydrogen phosphate precipitate through homogeneous nucleation, and then further oxidizing the precipitate slurry, an amorphous iron phosphate material with a low iron hydroxide content can be obtained. The amorphous iron phosphate material has a uniform particle size distribution, a low degree of agglomeration, and a small particle size. The applicant found in this study that the content of iron hydroxide affects the particle uniformity, agglomeration degree, and primary particle size of the amorphous iron phosphate material. When the content of iron hydroxide in the prepared amorphous iron phosphate material is low, it is beneficial to improve the uniformity of the particle size distribution of the amorphous iron phosphate material, reduce agglomeration, and reduce the primary particle size. After analysis, in this preparation method, due to the preferential synthesis of ferrous hydrogen phosphate precipitate, the formation of iron hydroxide crystal nuclei is suppressed, and the formed ferrous hydrogen phosphate solid can be used as a template to obtain amorphous iron phosphate with uniform particle distribution after oxidation. On the contrary, if the oxidation method is adopted first, iron hydroxide crystal nuclei are likely to be formed first, and phosphoric acid and iron ions grow rapidly on their surface and agglomerate in a small range to form iron phosphate particles. The amorphous iron phosphate formed has a large particle size and uneven particle distribution.

[0044] In the above-mentioned preparation method, the solution A containing a phosphorus source and a ferrous source can be prepared in a variety of ways, as long as it can satisfy the requirement that the phosphorus source and the ferrous source in the solution A do not undergo a precipitation reaction. For example, a phosphorus source solution can be prepared with a phosphorus source, and a solution can be prepared with a ferrous source as a raw material, wherein the ferrous source can be a water-soluble raw material or a water-insoluble raw material. When a water-insoluble raw material is used, an acid can be used to dissolve the water-insoluble ferrous source to obtain a ferrous solution, and then the two solutions are mixed to obtain solution A; a phosphorus source and a ferrous source can also be used as raw materials to prepare solution A while ensuring that the phosphorus source and the ferrous source do not undergo a precipitation reaction. Specifically, this can be achieved by adjusting and controlling the pH of the solution; wherein the pH adjuster can be an acidic solution or an alkaline solution, and the acidic solution can be sulfuric acid, hydrochloric acid solution, etc.; the alkaline solution can be ammonia water, urea solution, sodium hydroxide solution, etc.

[0045] In some preferred embodiments, the pH value of solution A is adjusted to 1.5-3.5, for example, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, etc.

[0046] In some embodiments, the reagent for adjusting the pH of solution A is one or more of ammonia water, urea, and sodium hydroxide.

[0047] In some preferred embodiments, the temperature of solution A is adjusted to 40-60 o C, for example 40℃, 45℃, 50℃, 55℃, 60℃, etc.

[0048] In some preferred embodiments, the phosphorus source is one or more of diammonium phosphate, phosphoric acid, and diammonium hydrogen phosphate; In some preferred embodiments, the ferrous source is one or more of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous oxalate, iron powder, and ferrous oxide; In some preferred embodiments, the molar ratio of phosphorus in the phosphorus source to iron in the iron source is 0.95-1.2:1.

[0049] In some preferred embodiments, the oxidant used in the oxidation is one or more of hydrogen peroxide, air, oxygen, and ozone.

[0050] After research, it was found that the amount of oxidant required for the preparation method of amorphous ferric phosphate provided by the present invention is lower than the amount of oxidant required by the existing preparation method. The amount of oxidant required by the existing preparation method is generally more than 1.4 times the theoretically required amount; in some preferred embodiments, the amount of the oxidant is 1.2 to 1.4 times the theoretically required amount, for example, 1.2 times, 1.3 times, or 1.4 times.

[0051] In some preferred embodiments, the mass percentage concentration of phosphorus in the solution A is 2% to 5%, for example, 2%, 3%, 4%, 5%, etc.

[0052] In some preferred embodiments, in the solution A, the mass percentage concentration of the iron element is 3% to 7%, for example, 3%, 4%, 5%, 6%, 7%, etc.

[0053] In some preferred embodiments, the pH value of the solution A is 0.5<pH<1.2, such as 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, etc. By making the solution A within the above pH range, it is ensured that the phosphorus source and the ferrous source do not undergo precipitation reaction.

[0054] In some preferred embodiments, the washing is performed with pure water; the conductivity of the washing water at the end point of the washing is not greater than 20000 μs / cm; In some embodiments, the mass fraction of water in the amorphous ferric phosphate is 25-40%, for example, 25%, 28%, 30%, 32%, 35%, 38%, 40%, etc.

[0055] The present invention also provides a method for preparing anhydrous ferric phosphate, comprising: The aforementioned amorphous ferric phosphate or the amorphous ferric phosphate prepared by the aforementioned preparation method is mixed with a phosphoric acid solution, heated for crystallization, filtered, washed with water, and calcined to obtain anhydrous ferric phosphate.

[0056] In the above technical scheme, since the amorphous iron phosphate prepared above is used as a template, the amorphous iron phosphate has a low iron hydroxide content, and thus has a uniform particle size distribution, a low degree of agglomeration, and a small particle size. Furthermore, after crystallization and calcination, the grain size and agglomeration of the amorphous iron phosphate are well continued, thereby being able to obtain anhydrous iron phosphate with a small particle size, a low degree of agglomeration, and a high specific surface area. The particle size of 95% of the primary particles of the anhydrous iron phosphate is below 90 nm, preferably 30 to 50 nm. The specific surface area is 9 to 14 m² / g, for example, 9 m² / g, 10 m² / g, 11 m² / g, 12 m² / g, 13 m² / g, 14 m² / g, etc., and the tap density is 0.7 to 1.0 g / cm³, for example, 0.7 g / cm³, 0.75 g / cm³, 0.8 g / cm³, 0.85 g / cm³, 0.9 g / cm³, 0.95 g / cm³, 1.0 g / cm³, etc.

[0057] The secondary particles of the anhydrous ferric phosphate have a D100 of 90 μm or less, more preferably 35-90 μm, for example 40 μm, 45 μm, 40 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, D99 of 50 μm or less, more preferably 20-50 μm, for example 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc., D90 of 7.5 μm or less, more preferably 4-7.5 μm, for example 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, etc., and D50 of 2-4 μm, for example 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, etc.

[0058] In the preparation method of anhydrous ferric phosphate, the molar ratio of phosphoric acid to amorphous ferric phosphate in the phosphoric acid solution can be conventionally controlled as long as the crystallization of the amorphous ferric phosphate can be achieved. In some embodiments, the ratio can be 0.02 to 0.2:1, for example, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.08:1, 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.20:1, etc.

[0059] In the preparation method of anhydrous ferric phosphate, the crystallization temperature corresponding to the temperature-raising crystallization is the conventional crystallization temperature in the art. In some embodiments, the temperature is 70 to 100 o C, for example, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.

[0060] In the preparation method of anhydrous ferric phosphate, pure water can be used for washing; the conductivity of the washing water at the end point of the washing is not greater than 1000 μS / cm.

[0061] In the preparation method of anhydrous ferric phosphate, the purpose of calcination is dehydration, and the conventional dehydration temperature in the art can be used; in some embodiments, the calcination temperature is 500-650 o C, for example, 500°C, 520°C, 550°C, 580°C, 600°C, 620°C, 650°C, etc.

[0062] The present invention also provides anhydrous ferric phosphate, which is prepared by the above-mentioned preparation method.

[0063] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0064] In the following embodiments and comparative examples, the tap density test method of the product is as follows: Take about 100g of the sample to be tested and put it into a 250mL measuring cylinder. Tap it 10 times, 500 times and 1250 times, and record the corresponding volumes V10, V500 and V1250, accurate to the smallest scale. If the difference between V500 and V1250 is less than 2mL, take V1250 as the tapped volume; otherwise, increase the number of taps until the difference between two consecutive recorded volumes is less than 2mL. Calculate the tapped density according to the formula m / V, where m is the sample mass and V is the tapped volume.

[0065] The test method for the specific surface area of ​​the product is as follows: The specific surface area was tested using a surface analyzer according to GB / T 13390-2008 Determination of specific surface area of ​​metal powders - Nitrogen adsorption method.

[0066] The test method for the particle size distribution of the product is as follows: Reference HG / T 4701 Iron phosphate for batteries 5.11 particle size determination method; mix the sample, weigh 0.1g sample, place it in a 100mL clean beaker filled with 50mL water, and then ultrasonicate for 15min and use Bettersize2600 laser particle size distribution analyzer wet method system for detection.

[0067] The method for testing the particle size range distribution of 95% of the primary particles in the product is as follows: The SEM images were imported into Image J software to obtain the particle distribution statistics. The particle statistics were fitted by the origin software to obtain the data distribution results. a±b is the 95% primary particle size range, where a and b are the mean and standard deviation, respectively.

[0068] Example 1 An aqueous solution containing 0.345 mol of ammonium dihydrogen phosphate was added to an aqueous solution containing 0.3 mol of ferrous sulfate, and sulfuric acid was added to adjust the pH of the mixed solution to 1.0 and the phosphorus-iron ratio to 1.15 to obtain a mixed solution in which the mass fraction of iron element was 6.0% and the mass fraction of phosphorus element was 3.5%. The mixed solution was heated to 50 o C, add ammonia water to adjust the pH to 2.66 to form an off-white ferrous hydrogen phosphate slurry; Hydrogen peroxide containing 0.21 mol of hydrogen peroxide was added to the above slurry for oxidation, and then filtered and washed until the conductivity of the washed water was no more than 20000 μS / cm to obtain iron phosphate yellow material. The obtained iron phosphate yellow material was subjected to X-ray diffraction detection, and the results were shown in the figure below. Figure 1 As shown, from Figure 1 It can be seen that the peak intensity ratio of the characteristic peak at 19-21° to the characteristic peak at about 28-30° is 0.852; the SEM image and particle distribution diagram of the obtained amorphous iron phosphate yellow material are shown in Figure 2As shown in the figure, it can be seen that the particles are evenly distributed, and the 95% primary particle size of the obtained amorphous iron phosphate is 32.7±4.5nm; The iron phosphate slurry and phosphoric acid were mixed, reacted at 95°C for 3 hours, the molar ratio of phosphoric acid to iron phosphate was 0.03, and filtered and washed with pure water until the conductivity of the washed water was no more than 1000 μS / cm; The filtered and washed product was dried and heated at 550 o C sintering for 2h to obtain anhydrous iron phosphate. The SEM image and particle distribution of anhydrous iron phosphate are shown in Figure 3 As shown in the figure, it can be seen that the 95% primary particle size of the obtained anhydrous ferric phosphate is 57.8±14.9nm, the size is consistent, and the specific surface area is 12.3m 2 / g, tap density 0.85g / cm 3 The X-ray diffraction test diagram of the obtained anhydrous iron phosphate is as follows: Figure 4 The secondary particle size is shown in Table 2.

[0069] Comparative Example 1 The raw materials and dosages used in this comparative example are exactly the same as those in Example 1, and the only difference is the preparation method, which specifically includes: A solution containing 0.345 mol of ammonium dihydrogen phosphate, a hydrogen peroxide solution containing 0.21 mol of hydrogen peroxide, and ammonia water are added to an acidic aqueous solution containing 0.3 mol of ferrous sulfate and stirred. The phosphorus-iron ratio is 1.15, the pH value of the reaction process control system is 2.2, and the reaction liquid temperature is 50°C. A yellow precipitate is obtained, which is filtered and washed until the conductivity of the washing water is no more than 20000 μS / cm to obtain iron phosphate yellow material. The obtained iron phosphate yellow material is subjected to X-ray diffraction detection, and the results are shown in the figure below. Figure 1 As shown, from Figure 1 It can be seen that the peak intensity ratio of the characteristic peaks at 19-21° and 28-30° is 0.917; the SEM image and particle distribution diagram of the obtained amorphous iron phosphate yellow material are as follows: Figure 5 As shown in the figure, it can be seen that the particle distribution is good, 95% of the primary particle size of the obtained amorphous iron phosphate is 133.98±27.8nm, the particle distribution is wide, and there is some agglomeration; The iron phosphate slurry and phosphoric acid were mixed, reacted at 95°C for 3 hours, the molar ratio of phosphoric acid to iron phosphate was 0.03, and filtered and washed with pure water until the conductivity of the washed water was no more than 1000 μS / cm; The filtered and washed product was dried and then sintered at 550°C for 2h to obtain anhydrous iron phosphate. The SEM image and particle distribution of anhydrous iron phosphate are shown in Figure 6 As shown in the figure, it can be seen that the 95% primary particle size of the obtained anhydrous ferric phosphate is 84.3±19.9nm, and the specific surface area is 8.2m 2 / g, tap density is 0.95g / cm 3 , slightly agglomerated. The X-ray diffraction detection diagram of the obtained anhydrous iron phosphate is as follows Figure 7 The secondary particle size is shown in Table 2.

[0070] In this comparative example, the obtained ferric phosphate yellow material and anhydrous ferric phosphate both have slight agglomeration. After analysis, the reason for the slight agglomeration may be: the divalent iron source, phosphorus source, ammonia water and hydrogen peroxide are mixed, wherein the formation of ferrous hydrogen phosphate and ferrous oxidation are carried out simultaneously, forming a competitive relationship, which can alleviate the formation of ferric hydroxide crystal nuclei and the growth of large yellow material particles to a certain extent. However, due to the presence of partial oxidation of ferrous ions to obtain trivalent ferrous ions, a certain amount of ferric hydroxide will be generated, phosphoric acid and ferric ions will grow rapidly on the surface of ferric hydroxide, agglomerate in a small range to form ferric phosphate particles, and then produce slight agglomeration; during subsequent crystallization, the inorganic acid can diffuse into the interior of the yellow material to remove impurities such as ferric hydroxide, and the morphology of the particles of the slightly agglomerated yellow material will not change greatly after crystallization, so the anhydrous ferric phosphate also has slight agglomeration.

[0071] Comparative Example 2 The raw materials and dosages used in this comparative example are exactly the same as those in Example 1, and the only difference is the preparation method, which specifically includes: Adding hydrogen peroxide containing 0.21 mol of hydrogen peroxide to an acidic aqueous solution containing 0.3 mol of ferrous sulfate to obtain a ferric sulfate solution; Mix the ferric sulfate solution and the aqueous solution containing 0.345 mol of diammonium phosphate, with an iron-phosphorus ratio of 1.15, and no precipitation is formed. Then add ammonia water dropwise, adjust the pH to 2.1, react, and the reaction temperature is 50°C. Filter and wash until the conductivity of the washing water is no more than 20000μS / cm to obtain iron phosphate yellow material. The obtained iron phosphate yellow material is subjected to X-ray diffraction detection, and the results are shown in the figure below. Figure 1 As shown, from Figure 1 It can be seen that the peak intensity ratio of the characteristic peaks at 19-21° and 28-30° is 0.951; the SEM image and particle distribution diagram of the obtained amorphous iron phosphate yellow material are shown in Figure 8 As shown in the figure, it can be seen that the particles are severely agglomerated and 95% of the primary particles of the obtained amorphous iron phosphate have a particle size of 165.8±51.2 nm or more.

[0072] The iron phosphate slurry and phosphoric acid were mixed, reacted at 95°C for 3 hours, the molar ratio of phosphoric acid to iron phosphate was 0.03, and filtered and washed with pure water until the conductivity of the washed water was no more than 1000 μS / cm; The filtered and washed product was dried and then sintered at 550°C for 2 hours to obtain the iron phosphate. The SEM image and particle distribution of the iron phosphate are shown in FIG. Fig. 9 As shown, from Fig. 9It can be seen that the 95% primary particle size of the obtained anhydrous iron phosphate is 166.3±62.1nm ( Fig. 9 ), after testing, the specific surface area is 5.3m 2 / g, tap density is 0.98g / cm 3 The X-ray diffraction test diagram of the obtained anhydrous iron phosphate is as follows: Fig.10 The secondary particle size is shown in Table 2.

[0073] In this comparative example, the obtained yellow iron phosphate material and anhydrous iron phosphate both have serious agglomeration phenomenon. After analysis, this may be because in the process of adding ammonia water, on the one hand, trivalent iron precipitates to form iron hydroxide, and on the other hand, trivalent iron reacts with the phosphorus source to form iron phosphate. However, since the nucleation rate of iron hydroxide nuclei is very fast, phosphate and iron ions grow rapidly on its surface, and agglomerate in a small range to form iron phosphate particles. The formed yellow iron phosphate material has a large particle size and uneven particle distribution. During the subsequent crystallization, the inorganic acid can diffuse into the interior of the yellow material to remove impurities such as iron hydroxide. Therefore, the morphology of the severely agglomerated yellow material will not change much after crystallization, resulting in severe agglomeration of the anhydrous iron phosphate.

[0074] Example 2 0.315 mol phosphoric acid was added to an aqueous solution containing 0.3 mol ferrous sulfate, and ammonia water was added to adjust the solution pH to 1.0, the phosphorus-iron ratio to 1.05, wherein the mass fraction of iron element was 6%, and the mass fraction of phosphorus element was 3.5%; Heat the mixed solution to 50 o C, add ammonia water to adjust the pH to 2.8 to form an off-white ferrous hydrogen phosphate slurry; Add hydrogen peroxide containing 0.21 mol of hydrogen peroxide to the slurry for oxidation, and then filter and wash until the conductivity of the washing water is no more than 20000 μS / cm to obtain yellow iron phosphate. The obtained amorphous yellow iron phosphate is tested by X-ray diffraction, and the peak intensity ratio of the characteristic peaks around 19-21° and 28-30° is 0.881, and the 95% primary particle size of the amorphous iron phosphate is 40.5±6.6 nm; Mix the iron phosphate slurry and phosphoric acid, 85 o C was reacted for 3 h, the molar ratio of phosphoric acid to iron phosphate was 0.03, and the mixture was filtered and washed with pure water until the conductivity of the washed water was no more than 1000 μS / cm; The filtered and washed product was dried and heated at 550 o C was sintered for 2 h to obtain the iron phosphate. After testing, 95% of the primary particles of the obtained iron phosphate were distributed in the range of 64.2±15.6 nm, and the specific surface area was 10.2 m 2 / g, tap density is 0.81g / cm 3 The particle size of the secondary particles of the obtained anhydrous ferric phosphate is shown in Table 2.

[0075] Example 3 Add an aqueous solution containing 0.303 mol of ammonium dihydrogen phosphate to an aqueous solution containing 0.3 mol of ferrous sulfate, add sulfuric acid to adjust the solution pH to 1.1, wherein the mass fraction of iron is 5%, the mass fraction of phosphorus is 2.8%; the phosphorus-iron ratio is 1.01, and heat the above solution to 50 o C, add sodium hydroxide to adjust the pH to 2.0 to form an off-white ferrous hydrogen phosphate slurry; Add hydrogen peroxide containing 0.18 mol of hydrogen peroxide to the above slurry for oxidation, react, and then filter and wash until the conductivity of the washing water is no more than 20000 μS / cm to obtain yellow iron phosphate. The obtained amorphous yellow iron phosphate is tested by X-ray diffraction. The peak intensity ratio of the characteristic peaks around 19-21° and 28-30° is 0.892, and the 95% primary particle size of the amorphous iron phosphate is 52.5±7.2 nm; The iron phosphate slurry and phosphoric acid were mixed and reacted at 85°C for 3 hours, with the molar ratio of phosphoric acid to iron phosphate being 0.03, and then filtered and washed with pure water until the conductivity of the washing water was no more than 1000 μS / cm; The filtered and washed product was dried and heated at 550 o C was sintered for 2 h to obtain the iron phosphate. After testing, 95% of the primary particles of the obtained iron phosphate were distributed in the range of 65.4±14.5 nm, and the specific surface area was 9.3 m 2 / g, tap density is 0.92g / cm 3 The particle size of the secondary particles of the obtained anhydrous ferric phosphate is shown in Table 2.

[0076] Example 4 Add an aqueous solution containing 0.345 mol of ammonium dihydrogen phosphate to an aqueous solution containing 0.3 mol of ferrous sulfate, add sulfuric acid to adjust the solution pH to 0.6, the mass fraction of iron element to 5.5%, the mass fraction of phosphorus element to 3.5%, and the phosphorus-iron ratio to 1.15, and heat the mixed solution to 50 o C, add ammonia water to adjust the pH to 2.66 to form an off-white ferrous hydrogen phosphate slurry; Oxygen was introduced into the slurry for oxidation at a flow rate of 900 mL / h for 2 hours for complete oxidation, and then filtered and washed with pure water until the conductivity of the washed water was no more than 20,000 μS / cm to obtain yellow iron phosphate. The obtained yellow iron phosphate was tested by X-ray diffraction, and the peak intensity ratio of the characteristic peak at 19-21° and the characteristic peak at about 28-30° was 0.871; the particles were evenly distributed, and 95% of the primary particles of amorphous iron phosphate had a particle size of 28.5±5.8 nm, with less agglomeration; The iron phosphate slurry and phosphoric acid were mixed, reacted at 95°C for 3 hours, the molar ratio of phosphoric acid to iron phosphate was 0.15, and filtered and washed with pure water until the conductivity of the washed water was no more than 1000 μS / cm; The filtered and washed product was dried and heated at 550 o C sintering for 2h to obtain anhydrous iron phosphate. The primary particle size distribution of 95% of the obtained iron phosphate is 61.5±13.8nm, and the specific surface area is 10.7m 2 / g, tap density is 0.88g / cm 3 The particle size of the secondary particles of the obtained anhydrous ferric phosphate is shown in Table 2.

[0077] Example 5 Add an aqueous solution containing 0.285 mol of ammonium dihydrogen phosphate to an aqueous solution containing 0.3 mol of ferrous sulfate, add sulfuric acid to adjust the solution pH to 0.6, the mass fraction of iron element to 3.8%, the mass fraction of phosphorus element to 2%, and the phosphorus-iron ratio to 0.95, and heat the mixed solution to 40 o C, add ammonia water to adjust the pH to 1.6 to form an off-white ferrous hydrogen phosphate solution; Add hydrogen peroxide containing 0.21 mol of hydrogen peroxide to the above slurry for oxidation, react, and then filter and wash until the conductivity of the washing water is no more than 20000 μS / cm to obtain yellow iron phosphate. The obtained amorphous yellow iron phosphate is tested by X-ray diffraction, and the peak intensity ratio of the characteristic peaks around 19-21° and 28-30° is 0.863, and the 95% particle size of the amorphous iron phosphate is 41.8±6.2 nm; The iron phosphate slurry and phosphoric acid were mixed, reacted at 95°C for 3 hours, the molar ratio of phosphoric acid to iron phosphate was 0.15, and filtered and washed with pure water until the conductivity of the washed water was no more than 1000 μS / cm; The filtered and washed product was dried and heated at 550 o C was sintered for 2 h to obtain anhydrous iron phosphate. The 95% primary particle size of the obtained anhydrous iron phosphate was 58.5±14.5 nm, and the specific surface area was 10.5 m 2 / g, tap density is 0.93g / cm 3 The particle size of the secondary particles of the obtained anhydrous ferric phosphate is shown in Table 2.

[0078] Example 6 Add an aqueous solution containing 0.348 mol of ammonium dihydrogen phosphate to an aqueous solution containing 0.3 mol of ferrous sulfate, add hydrochloric acid to adjust the solution pH to 1.1, the iron mass fraction is 7%, the phosphorus mass fraction is 4.5%, and the phosphorus-iron ratio is 1.16, and heat the mixed solution to 60 o C, add ammonia water to adjust the pH to 3.3 to form an off-white ferrous hydrogen phosphate solution; Add hydrogen peroxide containing 0.21 mol of hydrogen peroxide to the above slurry for oxidation, react, and then filter and wash until the conductivity of the washing water is no more than 20000 μS / cm to obtain iron phosphate yellow material. The obtained amorphous iron phosphate yellow material is subjected to X-ray diffraction detection, and the peak intensity ratio of the characteristic peaks around 19-21° and 28-30° is 0.876, and the 95% particle size of the obtained amorphous iron phosphate yellow material is 31.5±5.6 nm; The iron phosphate slurry and phosphoric acid were mixed, reacted at 95°C for 3 hours, the molar ratio of phosphoric acid to iron phosphate was 0.15, and filtered and washed with pure water until the conductivity of the washed water was no more than 1000 μS / cm; The filtered and washed product was dried and heated at 550 o C was sintered for 2 h to obtain anhydrous iron phosphate. The 95% primary particle size of the obtained anhydrous iron phosphate was 55.4±12.5 nm, and the specific surface area was 10.7 m 2 / g, tap density is 0.78g / cm 3 The particle size of the secondary particles of the obtained anhydrous ferric phosphate is shown in Table 2.

[0079] The ratio I1 / I2 of the characteristic peak intensity I1 at 19-21° and the characteristic peak intensity I2 at around 28-30° of the X-ray diffraction pattern of amorphous iron phosphate, the primary particle size of amorphous iron phosphate, the primary particle size of anhydrous iron phosphate and the specific surface area of ​​anhydrous iron phosphate are shown in Table 1.

[0080] It can be seen from Table 1 that compared with the amorphous iron phosphate prepared in each comparative example, the amorphous iron phosphate prepared in each embodiment has a lower ratio of the characteristic peak intensity I1 at 19-21° to the characteristic peak intensity I2 at around 28-30° in the X-ray diffraction pattern (i.e., the iron hydroxide content is lower), and the amorphous iron phosphate primary particles of each embodiment have a smaller particle size and a more uniform particle size distribution.

[0081] It can also be seen from Table 1 that, compared with the anhydrous ferric phosphate prepared in each comparative example, the anhydrous ferric phosphate prepared in each embodiment has a relatively higher specific surface area, a relatively narrower primary particle size distribution, a more uniform particle size distribution, and a smaller primary particle size; it can be seen that anhydrous ferric phosphate inherits the characteristics of the primary particles of amorphous ferric phosphate.

[0082] Table 1 Peak intensity ratio of amorphous iron phosphate and physical property parameter characterization of anhydrous iron phosphate It can be seen from Table 2 that compared with the anhydrous ferric phosphate prepared in each comparative example, the secondary particle size of the anhydrous ferric phosphate prepared in each example is smaller, indicating that the anhydrous ferric phosphate obtained in each example is relatively less agglomerated.

[0083] Table 2 Physical property parameters of secondary particles of anhydrous iron phosphate The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Amorphous iron phosphate, characterized in that The X-ray diffraction spectrum of the amorphous iron phosphate has a first diffraction peak θ1 and a second diffraction peak θ2 at 19-21° and 28-30°, respectively, and the ratio of the peak intensity I1 of the first diffraction peak to the peak intensity I2 of the second diffraction peak is 0.8-0.91; the amorphous iron phosphate is spherical or quasi-spherical particles.

2. The amorphous ferric phosphate according to claim 1, characterized in that The particle size of 95% of the primary particles of the amorphous iron phosphate is below 80 nm.

3. A method for preparing amorphous ferric phosphate, characterized in that: include: A solution A is prepared by using a phosphorus source and a ferrous source, and the pH value and temperature of the solution A are adjusted to react to obtain an off-white ferrous hydrogen phosphate slurry; The off-white ferrous hydrogen phosphate slurry is oxidized to obtain yellow amorphous ferric phosphate slurry, and the amorphous ferric phosphate is obtained by solid-liquid separation and washing.

4. The method for preparing amorphous ferric phosphate according to claim 3, characterized in that: The pH value of solution A is adjusted to 1.5-3.5; the reagent for adjusting the pH of solution A is one or more of ammonia water, urea, and sodium hydroxide; and / or, Adjust the temperature of solution A to 40~60 o C.

5. The method for preparing amorphous ferric phosphate according to claim 3, characterized in that: The phosphorus source is one or more of diammonium phosphate, phosphoric acid, diammonium hydrogen phosphate, and ammonium phosphate; and / or, The ferrous source is one or more of ferrous sulfate, ferrous chloride, ferrous nitrate, iron powder, ferrous oxide, and ferrous oxalate; The molar ratio of the phosphorus source calculated as phosphate to the ferrous source calculated as elemental iron is 0.95-1.2:

1.

6. The method for preparing amorphous ferric phosphate according to claim 3, characterized in that: The oxidant used in the oxidation is one or more of hydrogen peroxide, air, oxygen, and ozone; The amount of the oxidant used is 1.2 to 1.4 times the theoretically required amount.

7. The method for preparing amorphous ferric phosphate according to claim 3, characterized in that: In the solution A, the mass percentage concentration of phosphorus element is 2-5%; In the solution A, the mass percentage concentration of the iron element is 3-7%; The pH value of the solution A is 0.5<pH<1.2; The raw materials for preparing the solution A also include an acidic solution or an alkaline solution; The acidic solution is one or more of sulfuric acid and hydrochloric acid, and the alkaline solution is one or more of ammonia water, urea solution, and sodium hydroxide solution.

8. The method for preparing amorphous ferric phosphate according to claim 3, characterized in that: The washing is performed with pure water; preferably, the conductivity of the washing water at the end point of the washing is not greater than 20000 μS / cm.

9. Anhydrous ferric phosphate, characterized in that: The synthetic raw material is the amorphous iron phosphate described in claim 1 or 2 or the amorphous iron phosphate prepared by the preparation method described in any one of claims 3 to 8; The particle size of 95% of the primary particles of the anhydrous ferric phosphate is below 90 nm, and the specific surface area is 9-14 m 2 / g, tap density is 0.7~1.0g / cm 3 .

10. A method for preparing anhydrous ferric phosphate, characterized in that: include: The amorphous iron phosphate according to claim 1 or 2 or the amorphous iron phosphate prepared by the preparation method according to any one of claims 3 to 8 is mixed with a phosphoric acid solution, heated for crystallization, filtered, washed with water, and calcined to obtain anhydrous iron phosphate.

Citation Information

Patent Citations

  • Preparation method and application of amorphous iron phosphate

    CN112265974A

  • Method for preparing sulfur-free sodium-free battery grade iron phosphate by using ferrous sulfate

    CN115849320A

  • Iron phosphate and preparation method thereof, and lithium iron phosphate and preparation method thereof

    CN116768178A

  • Method for continuously producing battery-grade iron phosphate

    CN117285022A

  • Method for leaching and recovering lithium from waste lithium iron phosphate positive electrode powder

    CN118005051A

Cited By

  • A low-iron-phosphorus-ratio high-specific-surface-area iron phosphate material, a preparation method and applications thereof

    CN122585974A

  • Amorphous iron phosphate and preparation method therefor, and anhydrous iron phosphate and preparation method therefor

    WO2026114396A1